E-Modul Pembelajaran Pada Kewenangan Lembaga-Lembaga Negara dalam Pembelajaran PPKn - Ginting, Henny Krisnawati; Susanti, L.R. Retno; Chotimah, Umi (JKTP: Jurnal Kajian Teknologi Pendidikan, 2022)
This research aimed to develop e-module learning use flipbook maker on the authority of state institutions in learning Civics in the technical implementation unit of senior high school that is valid, practical and effective. This development method used the Rowntree development model which consisted of three stages, namely (1) planning; (2) writing preparation; (3) writing and editing. The evaluation used Tessmer’s evaluation stage, namely self evaluation, expert review, one to one, small group, and field test. The subjects of this research were X IPS 3 students of SMA Xaverius 1 Palembang. The validation results of e-module learning use flipbook maker by material, language and design experts obtained an average of 85,4 percent, so it was categorized as very valid. The practicality test results of e-module use flipbook maker in all groups obtained an average of 90,47 percent on one-to-one stage, and 85,71 percent on small group stage with a very practical category. The e-module learning effectiveness test results on student learning outcomes through an N-gain value was 0,7; it was the high category. Based on the research results, it can be concluded that the development of e-module learning use flipbook maker on the authority of state institutions in learning Civics in the technical implementation unit of senior high school has proven to be valid, practical and effective to be used in learning.AbstrakPenelitian ini bertujuan untuk mengembangkan e-modul pembelajaran menggunakan flipbook maker pada kewenangan lembaga-lembaga negara dalam pembelajaran PPKn di UPT SMA yang valid, praktis dan efektif. Metode pengembangan ini menggunakan model pengembangan Rowntree yang terdiri dari tiga tahapan, yaitu (1) perencanaan; (2) persiapan penulisan; (3) penulisan dan penyuntingan dan untuk evaluasi menggunakan tahap evaluasi yang dikembangkan oleh Tessmer yaitu (self evaluation, expert review, one to one, small group, dan field test). Subjek penelitian adalah peserta didik kelas X IPS 3 SMA Xaverius 1 Palembang. Hasil validasi e-modul pembelajaran menggunakan flipbook maker oleh ahli materi, bahasa dan desain memperoleh rata-rata 85,40 persen sehingga dikategorikan sangat valid. Hasil uji kepraktisan e-modul menggunakan flipbook maker pada semua kelompok diperoleh rata-rata 90,47 persen pada tahap one to one dan 85,71 persen pada tahap small group dengan kategori sangat praktis. Hasil uji efektivitas e-modul pembelajaran terhadap hasil belajar peserta didik dengan nilai N-gain sebesar 0,7 dengan kategori tinggi. Berdasarkan hasil penelitian ini maka dapat disimpulkan bahwa pengembangan e-modul pembelajaran menggunakan flipbook maker pada kewenangan lembaga-lembaga negara dalam pembelajaran PPKn di UPT SMA terbukti valid, praktis dan efektif digunakan dalam pembelajaran.